Mindfulness-based stress reduction (MBSR) and distress in a community-based sample - Evans, Susan; Ferrando, Stephen; Carr, Corey; Haglin, Dean (Clinical psychology and psychotherapy, 2011)
Background: Numerous studies have found Mindfulness‐based stress reduction (MBSR) to be useful for a wide range of problems including anxiety, pain and coping with a medical illness. The primary goal of this study was to evaluate the effectiveness of an 8‐week MBSR programme in relieving distress in a community based sample. Methods: Subjects (n = 14) were participants in the MBSR programme at a major academic medical center and completed the Profile of Mood States (POMS) and the Mindful Attention Awareness Scale (MAAS) prior to starting the class and at the end of the 8‐week course. Means and standard deviations were computed for the pre‐and post‐POMS total and subscale measures and the MAAS. Wilcoxon Signed Ranks Test was conducted. Results: There were significant reductions on multiple dimensions of distress on the POMS as well as a significant increase in mindful awareness as measured by the MAAS. Conclusion: These results suggest that MBSR appears to be associated with a reduction of distress and increased awareness of everyday life experiences in a sample of residents living in a large urban community. Copyright © 2010 John Wiley & Sons, Ltd. Key Practitioner Message: • Mindfulness‐based stress reduction (MBSR) appears to be an acceptable modality for mild to moderate psychological distress in a community sample. • Mindfulness training is associated with reduction in psychological distress. • Mindful Attention Awareness scale scores improved following an 8‐week MBSR course.